PERANCANGAN SISTEM INFORMASI PENGGAJIAN BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL PADA PT. ANUGERAH KARYA CIPTA - Yan Mitha Djaksana (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
The world has entered the era of information-based competition and it had become a valuable asset for business in winning its competition. Higher education also takes advantage of the information to streamline its academic process. PT. Augerah Karya Cipta is an online shopping based company and they keep developing every year, now the company has about 50 employees. PT. Augerah Karya Cipta is yet to be efficient in managing their employees’ salary as the number of their employees keep increasing. To redress the matter, they need a web-based information system and to successfully implement the idea, is to understand what the company need. Therefore, the writer chose “SISTEM INFORMASI PENGGAJIAN BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL PADA PT. ANUGERAH KARYA CIPTA” as the title, expected to simplify and to speed up the process of the company’s data regarding their employees’ salary.